Stimulating electrode Design for Implantable Sub Retina Research Application: A Novel Approach - Alavanthar, T; Ellappan, V (International Journal of Engineering and Technology, 2018)
This paper aims to study and converse the theoretical model of neural stimulation implant electrodes with the electrochemical aspects of design. The study investigates the practically realizable hypothetical model of minimal invasive retinal implant (miRI) stimulating electrodes for restoring lost sight of patients blinded by degenerative retinal diseases. The basic elemental methods of charge injection by the stimulation electrode to tissue are pointed out.  A prologue on the developments of vision implants and electrode characteristics were presented. We communicated the most important factors considered in this design stage of modeling, such as electrode position, size, impedance, charge injection capability, temperature change of the targeted retinal tissue and it’s surrounding for vision implant system. In this design, a mathematical model is created to investigate for the all above said factors which influence implants positioned at internal surface of the retinal tissue. This investigation gives an initial step in design verification before the fabrication.